Not to worry (most of the time). Issue 5 (15th April 2020) - Hagler, Donald J.
Key Points: Most (87.6%) of residual atrial L‐R shunts after Gore Cardioform septal occluder implant disappear by 12 months. Residual leaks at implantation were more common in larger defects with smaller retro‐aortic rims, and multiple fenestrations. While most residual defects close in 12 months, we unfortunately do not yet have a clear idea why or which of the 13% do not close.